Changing trends in causes of visual impairment and blindness among Bhutanese blind school students - Dechen Wangmo (Academia Medicine, 2025)
Childhood blindness is a major global public health issue, with an estimated 1.4 million children affected worldwide. Bhutan has an estimated childhood blindness prevalence of 0.38%. This study assesses the causes and trends of blindness and visual impairment (VI) among students enrolled in the Muenselling Institute for the Vision Impaired (MIK) in Bhutan. Using a cross-sectional descriptive approach, secondary hospital data were analyzed from pediatric ophthalmology and low-vision clinic records. A total of 51 students (mean age: 14.9 years, Standard deviation (SD): 4.4) were included. Of these, 17 (33.3%) had moderate VI, 8 (15.7%) had severe VI, and 25 (49%) were blind. Retinal diseases (43.1%) were the leading cause of VI and blindness, marking a shift from previous studies where lens pathologies were predominant. Hereditary factors accounted for 62.8% of cases, while 49% of conditions were avoidable. The emergence of Retinopathy of Prematurity (ROP) highlights the need for improved neonatal screening programs. Comparative analysis with past Bhutanese and regional studies indicates shifting etiologies. Strengthening early intervention, genetic counseling, and ROP screening programs is crucial for addressing childhood blindness in Bhutan.